Efficacy and cost-effectiveness of darbepoetin alfa once every 4 weeks versus continuous erythropoietin receptor activator once every 4 weeks for anemia correction in patients with chronic kidney disease not on dialysis - Geo Neul Park; Kyung Ho Lee; Ji Eun Moon; Soo Jeong Choi; Moo Yong Park; Jin Kuk Kim; Byung Chul Yu (The Korean Society of Nephrology, 2024)
Background For anemia management in patients with chronic kidney disease not on dialysis, darbepoetin alfa (DA), which has a shorter half-life but is more inexpensive than continuous erythropoietin receptor activator (CERA), is preferred in Korea. This study evaluated the efficacy, safety, and cost-effectiveness of once-in-4-weeks DA compared with once-in-4-weeks CERA in patients with chronic kidney disease not on dialysis. Methods In this randomized, prospective, non-inferiority study, 40 erythropoiesis-stimulating agent-naïve patients with chronic kidney disease not on dialysis were randomized 1:1 to the DA group and CERA group. They received the study drug once in 4 weeks during 10- or 12-week correction period and 24-week efficacy evaluation period. The primary outcomes were the mean difference in the changes in hemoglobin levels between baseline and efficacy evaluation period and hemoglobin response rates during the correction period. The secondary outcomes included differences in adverse events and costs. Results DA was non-inferior to CERA for anemia correction; the mean difference in the change in hemoglobin levels between the groups was -0.070 g/dL (95% confidence interval, -0.730 to 0.590 g/dL). Hemoglobin response rates were 100% with DA and 94.1% with CERA. Adverse events were comparable. The mean cost of DA was approximately one-third that of CERA (34,100 ± 7,600 Korean won/4 weeks vs. 115,500 ± 23,600 Korean won/4 weeks; p < 0.001). Conclusion Once-in-4-weeks DA safely corrects anemia in erythropoiesis-stimulating agent-naïve patients with chronic kidney disease not on dialysis and is more cost-effective than once-in-4-weeks CERA.